2006
DOI: 10.1134/s0006297906120108
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of DNA with cationic peptides: Conditions of formation and factors effecting internalization by mammalian cells

Abstract: This work was devoted to the study of conditions of the formation of DNA/K8 complex and analysis of factors effecting the entry of DNA/K8 complex into mammalian cells in comparison with DNA complexes with arginine-rich fragment (47-57) of human immunodeficiency virus (type 1) transcription factor Tat (Tat peptide). The stoichiometry of positively charged DNA/K8 complexes has been studied for the first time. Non-cooperative character of DNA-K8 interaction was revealed. It has been shown that along with the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The above phenomenon has been observed by others with TAT-conjugated macromolecular therapeutics. For example, Dizhe et al have reported increased cellular uptake of TAT/DNA complex in the presence of excess free TAT-peptide, and has attributed to a stimulatory effect of excess TAT-peptide on the cellular entry of TAT/DNA conjugate [42]. …”
Section: Discussionmentioning
confidence: 99%
“…The above phenomenon has been observed by others with TAT-conjugated macromolecular therapeutics. For example, Dizhe et al have reported increased cellular uptake of TAT/DNA complex in the presence of excess free TAT-peptide, and has attributed to a stimulatory effect of excess TAT-peptide on the cellular entry of TAT/DNA conjugate [42]. …”
Section: Discussionmentioning
confidence: 99%
“…The pCMVLacZ [Dizhe et al, 2006] and pA1(À256/þ72) [Lapikov et al, 2008] plasmids were described elsewhere. pCMVHNF4a, the expression vector of human transcription factor HNF4a, was a generous gift of Dr. Fukamizu (University of Tsukuba, Tsukuba, Japan).…”
Section: Plasmid Construction and Site-directed Mutagenesismentioning
confidence: 99%
“…The plasmid DNA was extracted by phenol:chloroform: isoamyl alcohol (25:24:1) pH 8 and precipitated with ethanol. The dried DNA pellet was reconstituted with TAE buffer and subjected to agarose gel electrophoresis [9,46].…”
Section: Resistance Of Peptide-dna Complexes To Dnase Imentioning
confidence: 99%
“…Heparin has a greater charge density compared to heparan sulfate [47] and is a stronger polyanion than DNA. Heparin is therefore, capable of displacing DNA from its complexes with polycations [46]. The peptide-DNA complexes responded differently on encountering heparin.…”
Section: Stability Of Peptide-dna Complexes In the Presence Of A Compmentioning
confidence: 99%